Політична відповідальність в місцевому самоврядуванні: уточнення змісту та актуальні аспекти дослідження - Тарасенко, Тетяна (My University, 2017)
The essence of the political responsibility is clarified and relevant aspects of the research in local government are highlighted. Attention is paid to the need for greater consideration of the possibility for political responsibility both to have and not to have a legal form. This feature is considered as a basisfor the classification of forms and mechanisms of political responsibility in local government. Summary of scientific approaches allowed specification of a political responsibility object in social relations associated with addressing the local issues and the impact of political responsibility on establishing the basic rules and regulations of local government activity. The importance of the further disclosure of political responsibility functions in ensuring democratic, responsible governance at the local level is stated. Results of the research allow to determine the theoretical basis for further study of forms and mechanisms of this kind of responsibility in local government in Ukraine.
Political responsibility in local government: content and relevant aspects of research
Keywords: публічне управління; місцеве самоврядування; децентралізація; державне управління; політична відповідальність; political responsibility; public administration; local government; responsible localgovernance